1993
DOI: 10.1073/pnas.90.16.7864
|View full text |Cite
|
Sign up to set email alerts
|

The SCL gene product is regulated by and differentially regulates cytokine responses during myeloid leukemic cell differentiation.

Abstract: Differentiation induction in murine Ml leukemia cells by interleukin 6 (IL-6), leukemia inhibitory factor (LIF), and oncostatin M (OSM) is postulated to occur via a common receptor chain, gpl3O. In this study, growth factorinduced differentiation of Ml cells was accompanied by a late and persistent decrease in levels of mRNA and protein for a helix-oop-helix transcription factor, the SCL gene product. (18,(21)(22)(23). Despite differences in these receptor complexes, receptor signaling for IL-6, LIF, and OSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…This result is notable, since OSM and LIF both utilize the LIFR-gp130 heterodimer for signalling, and at least in some situations elicit an identical biological response (Tanigawa et al, 1993). The di erence between OSM and LIF in MCF-7 cells may be attributable to an OSM-speci®c receptor subunit.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is notable, since OSM and LIF both utilize the LIFR-gp130 heterodimer for signalling, and at least in some situations elicit an identical biological response (Tanigawa et al, 1993). The di erence between OSM and LIF in MCF-7 cells may be attributable to an OSM-speci®c receptor subunit.…”
Section: Discussionmentioning
confidence: 93%
“…For IL-6 and IL-11 it appears that intracellular signalling is mediated via a homodimer of gp130 while LIF, OSM and CNTF utilise the heterodimer between LIF and gp130. Although signalling through these complexes is very similar, they can be distinguished in some systems (Tanigawa et al, 1993(Tanigawa et al, , 1995. These observations have provided a unifying concept to explain the biological redundancy of these growth-factors.…”
Section: Introductionmentioning
confidence: 99%
“…Gene targeting experiments have shown that scl is essential for the initiation of yolk sac haemopoiesis (Robb et al, 1995a;Shivdasani et al, 1995). In addition to this role in early haemopoiesis, experiments in tissue culture have provided evidence that scl is important at later stages of haemopoiesis for normal erythroid and monocytic lineage commitment and di erentiation (Green et al, 1991;Aplan et al, 1992;Tanigawa et al, 1993). Transcriptional regulation by scl may, in part, be controlled by the presence of scl-binding partners such as E12, E47 (Hsu et al, 1994) and LMO-2 (Valge-Archer et al, 1994;Wadman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, in ordinary primary culture, lipid droplets and vitamin A fluorescence disappear within several days when Ito cells are cultured without vitamin A. 11,17 In this study, oil-red O staining showed lipid droplets within the cells, and fluorescence microscopy examined by reverse-transcription PCR, whereas M1/SCL cells 12,13 (in which SCL expression is enhanced) served as positive control.…”
Section: [ 3 H]vitaminmentioning
confidence: 99%